(untitled) - George, Edwin F. (Edington, U.K., 1993)
Part one of a two-part reference offering a comprehensive encyclopaedia on a specialized, but established method of plant propagation. This edition has been completely revised and expanded to give full author accreditation, with a bibliography amounting to over 9000 literature citations.
Chọn tạo và nhân giống vô tính
Keywords: Plant propagation,Nhân giống thực vật